Conversion and reversion of anti‐John Cunningham virus antibody serostatus: A prospective study - Michael Auer (Brain and Behavior, 2019)
Abstract Introduction Determination of antibodies against the John Cunningham virus (JCV) is an important tool for risk stratification in Natalizumab‐treated multiple sclerosis (MS) patients. Six‐monthly testing has been suggested for anti‐JCV antibody negative patients and patients with low antibody index in order to detect changes of serostatus. We conducted a prospective study with predefined testing intervals in order to investigate the predictability of anti‐JCV antibody status and the intervals for repetitive testing. Methods Our study included 109 patients at the MS Clinic of the Departments of Neurology, Medical Universities of Innsbruck and Salzburg. Blood withdrawals were performed at five time points: baseline, month 1, 3, 6, and 12. Patients’ sera were sent to Unilabs, Copenhagen, Denmark, where anti‐JCV antibodies were tested by a two‐step enzyme‐linked immunosorbent assay. Qualitative (negative/positive) and quantitative results (anti‐JCV antibody index) were used for statistical analyses. Results In our cohort, 52.3% of the patients were positive for anti‐JCV antibodies at baseline, with a significant correlation with age, but no association with sex or prior disease‐modifying therapy. Seven patients converted and reverted from negative to positive status and vice versa around the cut‐off index of 0.4, but no patient showed a permanent seroconversion from negative to highly positive anti‐JCV antibody status. Conclusion Long‐term anti‐JCV antibody status, including seroconverters/‐reverters around the cut‐off index, is highly predictable by testing three times within short intervals, however, we cannot suggest clearly defined intervals for repetitive testing. The rate of real seroconverters, i.e., new infections with JCV, per year seems lower than previously described.